Subcutaneous Emphysema, Pneumomediastinum, Pneumoretroperitoneum, and Pneumoscrotum: Unusual Complications of Acute Perforated Diverticulitis. (17th July 2014) - Fosi, S.; Giuricin, V.; Girardi, V.; Di Caprera, E.; Costanzo, E.; Di Trapano, R.; Simonetti, G.
Abstract : Pneumomediastinum, and subcutaneous emphysema usually result from spontaneous alveolar wall rupture and, far less commonly, from disruption of the upper airways or gastrointestinal tract. Subcutaneous neck emphysema, pneumomediastinum, and retropneumoperitoneum caused by nontraumatic perforations of the colon have been infrequently reported. The main symptoms of spontaneous subcutaneous emphysema are swelling and crepitus over the involved site; further clinical findings in case of subcutaneous cervical and mediastinal emphysema can be neck and chest pain and dyspnea. Radiological imaging plays an important role to achieve the correct diagnosis and extension of the disease. We present a quite rare case of spontaneous subcutaneous cervical emphysema, pneumomediastinum, and pneumoretroperitoneum due to perforation of an occult sigmoid diverticulum. Abdomen ultrasound, chest X-rays, and computer tomography (CT) were performed to evaluate the free gas extension and to identify potential sources of extravasating gas. Radiological diagnosis was confirmed by the subsequent surgical exploration.